2014
DOI: 10.1038/pcan.2014.47
|View full text |Cite
|
Sign up to set email alerts
|

Synergism between metformin and statins in modifying the risk of biochemical recurrence following radical prostatectomy in men with diabetes

Abstract: The combination of statins and metformin in men undergoing RP for prostate cancer (PCa) may be associated with a lower BCR risk than would be predicted based on the independent effects of both medications. A synergism between these two agents is biologically plausible based on our current understanding of their diverse molecular pathways of action. The results of future clinical trials involving the use of either medication in men with PCa should be carefully assessed for confirmatory evidence of such a relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 32 publications
1
20
0
Order By: Relevance
“…Given data that other commonly used medicines may be associated with lower PC risk 15, 16 and the high frequency of PDE-5i use in older men (i.e. those at greatest risk for PC), several studies examined the relationship between PDE-5i use and PC with conflicting results.…”
Section: Discussionmentioning
confidence: 99%
“…Given data that other commonly used medicines may be associated with lower PC risk 15, 16 and the high frequency of PDE-5i use in older men (i.e. those at greatest risk for PC), several studies examined the relationship between PDE-5i use and PC with conflicting results.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical trials to investigate treatment with statins in combination with other agents are warranted, particularly combinations with compounds that show synergy with statins in animal models and whose mechanism of synergistic activity is known. Indeed, a study published in 2015 in 767 diabetic men with prostate cancer undergoing radical prostatectomy found that combined treatment with statins and metformin, but neither statin nor metformin use alone, resulted in a significantly reduced risk of biochemical recurrence during a follow-up period of 27 months ( P = 0.037 for combined statin and metformin use, P = 0.676 for statin use alone and P = 0.117 for metformin use alone) 113 . Liver X receptor agonists are a group of other potential candidates for combination treatments with statins.…”
Section: Future Perspectivementioning
confidence: 99%
“…We required criterion (ii) to eliminate potential effects associated with TZD or insulin use on cancer incidence as reported in the literature. (23,24) In addition, to account for the potential interactions between metformin with statin and finasteride,(69) we limited the cohort to 76,733 men who (i) have had prescription(s) of statins for ≥180 days or none; and (ii) have had prescription(s) of finasteride for ≥180 days or none. All study procedures were approved by the Institutional Review Board of the University of Texas Health Science Center at San Antonio and the Research and Development Committee of the South Texas Veterans Health Care System at San Antonio.…”
Section: Methodsmentioning
confidence: 99%
“…Predictors in this Cox model included indicators of race/ethnicity groups (AA and Hispanics) with NHW being the referent, indicators of statin use (6,7,9) and finasteride use,(28) age, change in LDL, HbA1c, and BMI, and the maximum PSA level during the study period. Under this Cox regression model, the impact of race/ethnicity was assessed by the hazard ratio (HR) associated with AA or Hispanic group relative to the NHW group.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation